2013
DOI: 10.1007/s11916-013-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Considerations in Migraine Management: Does a Consistent Diet Improve Migraine?

Abstract: The clinical expression of migraine is significantly impacted by dietary and gastrointestinal issues. This includes gut dysfunction during and between attacks, food triggers, increase in migraine with obesity, comorbid GI and systemic inflammation influenced by diet, and specific food allergies such as dairy and gluten. Practitioners often encourage migraineurs to seek consistency in their lifestyle behaviors, and environmental exposures, as a way of avoiding sudden changes that may precipitate attacks. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…Inflammation at the level of the trigeminovascular system is hypothesized to play a role in migraine pathophysiology and could be influenced by inflammation and immune modulation in the GI tract and systemically as evidenced by recent studies [90,91]. Likewise, there is evidence to suggest that the gut microbiota plays an important role in the brain-gut axis and aberrancies may be associated with neurological disease like migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation at the level of the trigeminovascular system is hypothesized to play a role in migraine pathophysiology and could be influenced by inflammation and immune modulation in the GI tract and systemically as evidenced by recent studies [90,91]. Likewise, there is evidence to suggest that the gut microbiota plays an important role in the brain-gut axis and aberrancies may be associated with neurological disease like migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly cited dietary triggers include chocolate, cheese, processed meats, and red wine; however, to date, there are no studies which unequivocally support the role of specific foods in migraine. Yet, elimination diets are often clinically recommended to mitigate migraine attacks . Other investigations suggest that eating frequency, meal timing, and the macronutrient composition of the diet may also play a role in migraine .…”
mentioning
confidence: 98%
“…Many studies evaluated the effect of single or multiple dietary factors on migraine . Moreover, there is some evidence to indicate the positive effect of high diet quality on migraine management . So, this study compared the diet quality of women with CM and EM.…”
Section: Discussionmentioning
confidence: 99%
“…Evans and colleagues have revealed significant differences between the diet quality of women with and without migraine and suggested that improving diet quality may be effective as part of the migraine treatment process . In addition, some evidence indicates that a higher consumption of healthy food items including fruits, vegetables, and whole grains and a lower consumption of fats might be effective in reducing migraine severity and attack frequency …”
Section: Introductionmentioning
confidence: 99%